Advances in contact linguistics in honour of Pieter Muysken - Smith, Norval; Veenstra, Tonjes, 1962-; Aboh, Enoch Oladé; Muysken, Pieter (Contact language library ;, 2020)
"Issues in multilingualism and its implications for communities and society at large, language acquisition and use, language diversification, and creative language use associated with new linguistic identities have become hot topics in both scientific and popular debates. A ubiquitous aspect of multilingualism is language contact. This book contains twelve articles that discuss specific aspects of Contact Linguistics. These articles cover a wide range of topics in the field, including creoles, areal linguistics, language mixing, and the sociolinguistic aspects of interactions with audiences. The book is dedicated to Pieter Muysken whose work on pidgin and creole languages, mixed languages, code-switching, bilingualism, and areal linguistics has been ground-breaking and inspirational for the authors in this book, as well as numerous other scholars working on the various facets of this rapidly expanding field"--